Study of the level of physical fitness of young acrobat athletes at the initial stage of training - Tetiana Chernykh; Vyacheslav Mulik; Daria Okun (Kharkiv State Academy of Physical Culture, 2019)
Purpose: determine the level of physical preparedness of young acrobat athletes of the first year of training. Material & Methods: the study was conducted on the basis of the Integrated Children's Sports School No. 6 of the Sloboda district (Kharkiv). The study involved 16 children 5-6 years old, engaged in sports acrobatics in sports and fitness groups. Enrollment in primary training groups was carried out in accordance with the regulations established by the administration of the children's sports school. Pedagogical testing of physical and functional-motor readiness of children was carried out using tests provided by the State standard of sports training in sports acrobatics to assess general and special physical preparedness. The level of speed strength, special flexibility in the hip joint and spinal column, dynamic strength, speed, static strength were determined. Results: using correlation analysis, it was established that there are interconnections of a predominantly average level between the indicators of general and special physical preparedness of young athletes. Conclusions: studies have established that young beginner acrobats have a high level of flexibility, other indicators of physical qualities have heterogeneous results, mainly of an average level of correlation between exercises of general and special physical fitness.